A Comparison Theorem for Stability of Linear Stochastic Implicit Difference Equations of Index-1 - Hong Son, Nguyen (VNU Journal of Science: Mathematics - Physics, 2020)
In this paper we study linear stochastic implicit difference equations (LSIDEs for short) of index-1. We give a definition of solution and introduce an index-1 concept for these equations. The mean square stability of LSIDEs is studied by using the method of solution evaluation. An example is given to illustrate the obtained results.